EFFECT OF THE ALTAN OINTMENT ON MORPHOLO-GICAL CONDITION OF THE PERIODONTAL TISSUES OF RATS AFTER LONG-LASTING TRAUMATIC FACTOR - Chechotina, S.Yu. (World of Medicine and Biology, 2013)
The results of histological examination of periodontal tissues of white rats following long-lasting traumatic factors under the application of 2% altan ointment were presented in the study. The morphological structure of the periodontal tissues of the intact rat are not fundamentally different from similar formation in humans. On histological preparations of the control group of rats after long-lasting traumatic factor revealed deep destructive processes in periodontal tissues. The use of altan ointments for 10 days for the treatment of traumatic periodontitis in rats increased the regenerative processes in the injured periodontal tissues, that will provide a consolidation of ligamentous apparatus of tooth in the future.
Keywords: periodontal tissues of rats; traumatic parodontitis; altan ointment